2017
DOI: 10.3389/fmicb.2017.01261
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Enterococcus mundtii Isolate Protects the Model Insect Tribolium castaneum against Bacillus thuringiensis

Abstract: Enterococcus mundtii strains isolated from the larval feces of the Mediterranean flour moth Ephestia kuehniella show antimicrobial activity against a broad spectrum of Gram-positive and Gram-negative bacteria. The in vitro probiotic characterization of one isolate revealed a high auto-aggregation score, a hydrophilic cell surface, tolerance for low pH, no hemolytic activity, and susceptibility to all tested antibiotics. We used the red flour beetle Tribolium castaneum, an established model organism, for the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 96 publications
1
43
0
Order By: Relevance
“…The composition of the microbial community of an organism can be altered through rearing conditions (e.g. a probiotic diet), via a breeding regime or by genetic manipulation (Grau, Vilcinskas, & Joop, 2017; Ras et al ., 2017). For example, D. melanogaster fed a probiotic bacterium were less susceptible to infections of pathogenic bacteria (Blum et al ., 2013).…”
Section: How Can Genetics Be Used To Improve Biological Control?mentioning
confidence: 99%
“…The composition of the microbial community of an organism can be altered through rearing conditions (e.g. a probiotic diet), via a breeding regime or by genetic manipulation (Grau, Vilcinskas, & Joop, 2017; Ras et al ., 2017). For example, D. melanogaster fed a probiotic bacterium were less susceptible to infections of pathogenic bacteria (Blum et al ., 2013).…”
Section: How Can Genetics Be Used To Improve Biological Control?mentioning
confidence: 99%
“…E. raffinosus which was reported to prevent bacterial infection in Labeo rohita and Labeo catla from E. coli, A. hydrophilla, S. aerous, S. typhimurium [43]. The identified E. hirae, reported producing lipase and bile salt hydrolase enzyme with antioxidant properties, and E. mundtii reported with antimicrobial activity [44]. Four Roseobacter spp., identified from the sediment metagenomes, were reported with therapeutic value for commercial aquaculture.…”
Section: Plos Onementioning
confidence: 95%
“…Such bacteria are widely used as animal feed additives in food production [ 129 ]. Enterococcus mundtii bacteria isolated from the feces of Ephestia kuehniella have the function of protecting the flour beetle, Tribolium castaneum , against Bt infection [ 130 ]. The surface properties test showed that this isolate has intense levels of auto-aggregation, which is related to the formation of colonies in the host insect’s gut [ 131 ].…”
Section: The Interaction Between Bt and Host Gut Microbiotamentioning
confidence: 99%
“…Moreover, bacteria cell wall compounds, such as lipopolysaccharide (LPS) and peptidoglycan (PGN), have been well studied, and can stimulate the host immune response [ 132 , 133 ]. However, Tribolium castaneum larvae exposed to the corresponding supernatant can also increase the resistance to Bt infection [ 130 ]. This perhaps suggests that the protective function of probiotic bacteria is based on the secreted proteins or some small peptides, which may act directly against Bt infection or through the triggering of immune priming.…”
Section: The Interaction Between Bt and Host Gut Microbiotamentioning
confidence: 99%